Etika Bermusyawarah Menurut Al-Qur'an - Mujetaba Mustafa (TASAMUH: Jurnal Studi Islam, 2015)
The Holy quranic texts are guidance in the life of Muslim society. The position of Quran is perfect from the holy texts before it should be guidance a long a live. Musawarrah is a media of Ummah to share the opinion and intrest. To solve of Musawarah from destroy we should sport to apply in our live. From study of ayah Musawarah in holy quranic texts, there are many ayat explore, QS al-Baqarah 233, QS. Ali Imran, 159, and QS As-Syra’ 23. All of context of ayat Musawarrah tend to give the opinion, listening opinion the other dan respect them opions as positive contribution. The proses of Musawarah in Quran, like a bee rising a honey. It’s sweet for, if all of member of Musawarah listening and respect